Broad vs. narrow traits: a scoping review of measuring personality traits in teacher selection using the situational judgment test - Nadmilail, Azad Iqram; Mohd Matore, Mohd Effendi Ewan; Maat, Siti Mistima; Sheridan, Lynn (Frontiers in Psychology, 2023)
Situational Judgement Tests (SJTs) have gained popularity and are commonly used as a measurement technique in a variety of professions, particularly those that include hiring, promoting, and professional development. In various educational sectors around the world, SJTs are being utilized as a measure by which to choose individuals who possess the requisite non-academic attributes for the profession. The objective of this review is to identify and analyze the traits that are measured in teacher selection using SJTs, in terms of both broad and narrow traits. This review uses a scoping review approach comprising five stages which are: identifying the research question, identifying relevant studies, selecting the studies, charting the data and reporting the results. Seven empirical research studies on teacher selection using SJTs were identified in which broad and narrow traits are used differently in selection. In the studies, a broad traitconscientiousnessand seven narrow traitsorganization and planning; empathy and communication; adaptability and resilience; mindset; emotional regulation; professional ethics; and enthusiasm and motivationwere recognized. Analysis revealed, in line with other prior studies, that the traits discovered tended to be used as the foundation for teacher selection criteria. The use of broad and narrow traits as the basis for teacher selection criteria has implications for the selection of the 'best' teacher candidates because both broad and narrow traits generally do not accurately measure the precise characteristics needed. Future studies should focus on measuring more precise characteristics without overlap between the targeted characteristics, in light of the conclusions from this review.